Congenital dysfibrinogenaemia assessed by whole blood thromboelastography. (30th April 2018) - Wei, A.; Liao, L.; Xiang, L.; Yan, J.; Yang, W.; Nai, G.; Luo, M.; Deng, D.; Lin, F.
Abstract: Introduction: Congenital dysfibrinogenaemia (CD) is a rare hereditary blood disorder, and thromboelastography (TEG) can comprehensively assess the clotting function of patients. However, only few studies have focussed on the application of TEG in CD. We aim to investigate the clinical value of TEG in congenital CD. Methods: We performed TEG and routine coagulation tests, including plasma prothrombin time (PT), activated partial thromboplastin time (APTT), thrombin time (TT), functional fibrinogen (Fg) concentration (Clauss method) and Fg concentration (PT‐derived method) tests, in 17 patients with CD (experimental group) and 28 healthy individuals (control group). Results: In the TEG test, the coagulation time was significantly longer and the angle value was significantly smaller in the experimental group than that in the control group (3.73 ± 1.73 minutes vs 1.99 ± 0.49 minutes; 52.39°±11.6° vs 65.69°±4.43°; P  <   .05 for both); the coagulation index was significantly decreased in the experimental group when compared to the control group (−0.86 ± 2.85 vs 1.29 ± 1.53) ( P  <   .05), but the maximum amplitude was not significantly different ( P  >   .05). In the coagulation test, compared with the control group, TT was significantly longer (11.59 ± 0.93 minutes vs 32.34 ± 7.1 minutes; P  <   .05) and the functional Fg concentration was significantly lower (3.17 ± 0.59 g/L vs 0.56 ± 0.18 g/L; P  <   .05) in the experimental group, whereas there were no differences in APTT, PT and Fg concentrations ( P  >   .05). Conclusion: TEG is highly accurate for detecting coagulation function in patients with CD, with the thromboelastographic coagulation time and angle reflecting a reduced Fg activity, thereby facilitating diagnosis and differential diagnosis of CD and coagulation status evaluation of patients with CD.